The Performance Of The Executive Power And The Structure Of The Legal Order - Rubio, Marcial (1978)
The objective of this work is to systematize, at the level of the structure of the legal order, the administrative and governmental acts realized by the executive power, which has become more confused with the public administration, which is only one of its parts. We are interested in treating the problem from the legal point of view, which implies focusing in the legal forms that the actions of officials and rulers assume. In this sense, we deal basically with existing problems in decrees and resolutions of different kinds, and the possible solution lines in the constitutional plane as in the legislative.